Initial clinical experience with VersaCross transseptal system for transcatheter mitral valve repair. Issue 6 (11th November 2020) - Sayah, Neila; Simon, Francois; Garceau, Patrick; Ducharme, Anique; Basmadjian, Arsene; Bouchard, Denis; Pellerin, Michel; Bonan, Raoul; Asgar, Anita W.
Abstract: Objectives: The aim of this study is to describe the initial experience with versacross transseptal (TS) system for transseptal puncture for the transcatheter mitral valve repair using the MitraClip device. Background: Transeptal puncture is a key step in transcatheter mitral valve repair (MVR) and the use of the VersaCross system comprised of a sheath, a dilator and a radiofrequency wire has not been previously described. Methods: Prospective single center study of consecutive patients undergoing transcatheter mitral valve repair with the MitraClip device were included. Targeted TS puncture was performed under transesophageal echocardiographic (TEE) guidance. Baseline demographics, procedural characteristics, and major adverse procedural events were collected. Results: Twenty‐five consecutive patients underwent transseptal puncture using the VersaCross TS system. Transseptal puncture was successful in 100% of patients. The mean time for TS puncture was 3 3 ± 1.6 min with no major adverse procedural events. The mean time from insertion of the VersaCross system to insertion of the MitraClip guide catheter was 3.8 ± 3.0 minutes. Conclusion: The VersaCross TS system was successful in all patients for MitraClip procedure with no adverse procedural events and may be associated with increased procedural efficiency.